EFEKTIVITAS LAYANAN BIMBINGAN KLASIKAL TERHADAP PEMAHAMAN DIRI PESERTA DIDIK KELAS VII.1 DI SMP NEGERI 3 BUKITTINGGI - Siti Aisyah; Syawaluddin Syawaluddin; Bobi Tourist Yursa (CV. ADIBA AISHA AMIRA, 2023)
Self-understanding is an understanding of an individual's self to gain potential about himself, how he can recognize his potential, both physical and psychological potential, so that the student is able to understand the direction and purpose of his life. The aim of this research is to test the effectiveness of classical guidance services on the understanding of class VII.1 students at SMP Negeri 3 Bukittinggi. The researcher used a pre-experimental research method approach, one group pre-test post-test. The population in the research were all students in class VII.1 at SMP Negeri 3 Bukittinggi who did not yet fully understand themselves. The data analysis technique uses the Wilcoxon Rank Test. The instrument used is the questionnaire. Analysis of the Wilcoxom Rank Test shows that the value 0.00 is lower than 0.05. So it is concluded that the application of classical guidance services to the self-understanding of class VII.1 students at SMP Negeri 3 Bukittinggi is increasing and being provided effectively.